Interpretation of non‐verbal cues by people with and without TBI: understanding relationship intentions. Issue 3 (15th November 2018) - Evans, Kelli J.; Evans, David L.
Abstract: Background: Although long‐term social challenges following traumatic brain injury (TBI) are well documented, the challenges of establishing new relationships following TBI are less understood. Aims: To examine how the type of non‐verbal cues produced by an unfamiliar communication partner impacts feelings of relationship closeness by people with and without TBI. Methods & Procedures: In this quasi‐experimental comparative mixed‐group design, participants included 12 male heterosexual adults with moderate/severe TBI and 10 typical comparison peers. An adaptation of the Relationship Closeness Induction Task (RCIT), a 29‐item questionnaire, was completed by all participants to induce relationship closeness through reciprocal self‐disclosure during conversation. Participants completed the RCIT three separate times in counterbalanced order. Conversational partners for the RCIT were three female actors trained to convey similar verbal answers to the RCIT questions, but to produce different non‐verbal cues: solicitation (i.e., flirting), neutral and rejecting. Following each conversation, the participants completed a 10‐item Likert‐type questionnaire about the experience. Outcomes & Results: Between‐ and within‐group non‐parametric statistical analysis of Likert questions showed non‐significant differences between the two participant groups such that both groups consistently rated the female actor who used flirting non‐verbal cues higher than the actor who used rejecting non‐verbal cues. Conclusions & Implications: These results suggest a small sample of heterosexual males with TBI interpret non‐verbal relationship cues in real‐time conversations with unfamiliar partners as well as comparison peers. Clinical implications include the need to consider real‐time conversation in assessment and treatment planning for social communication goals related to cognitive–communication impairment.